Improving the 3D printability of high volume fly ash mixtures via the use of nano attapulgite clay - Panda, Biranchi (2020)
The effect of nano-attapulgite clay (NC) addition on the fresh, hardened and microstructural properties of high volume fly ash (HVFA) mixes designed for 3D printing was investigated in this study. Experimental results showed that the addition of 0.1–0.5% (i.e. by mass of binder) NC increased the static yield stress of HVFA mortars without significantly affecting the apparent viscosity, due to particle re-flocculation and enhanced thixotropy. When compared to the control mix, the use of 0.5% NC also led to increased viscosity recovery and improved structural build-up at different resting times and shear rates. These advancements were useful for 3D concrete printing, during which the material should be extrudable and buildable layer-by-layer without any deformation. Successful implementation of mixes containing NC was demonstrated via the printing of a 20-layer structure. Further optimization of the NC content and associated HVFA mix design is recommended, depending on the geometrical and mechanical properties required.